PREDICTION OF STUDENT ACHIEVEMENT BASED ON PARENTAL INCOME AND ATTENDANCE OF CLASS IX STUDENTS USING MULTIPLE LINEAR REGRESSION METHOD - Tarigan, Adelia Br; Lubis, Dara Muna; Silvina, Nur; Tampubolon, Rafael; Farhana, Nurul Ain; Manulang, Sudianto (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
This study aims to predict student achievement based on parental income and attendance. This study uses a quantitative approach with the population included all ninth grade students at SMP Swasta YP Utama Medan and the sample taken was 25 students. This study used instruments in the form of questionnaires and documentation. Data analysis used multiple linear regression to predict student academic achievement based on the variables of parental income and attendance. Prediction of students' achievement in grade IX at SMP Swasta YP Utama Medan based on parents' income and attendance patterns resulted in a Multiple Linear Regression equation that shows a positive relationship between economic conditions, students' attendance patterns and students' academic achievement. The accuracy level of prediction of student academic achievement based on parental income and attendance patterns shows that there are 16% of students getting excellent and 84% of students getting good grades